FOWLING IN LOWLANDS – NEOLITHIC AND CHALCOLITHIC BIRD EXPLOITATION IN SOUTH-EAST ROMANIA AND THE GREAT HUNGARIAN PLAIN. Archaeolingua, Series Minor 24. Budapest. 152 pp. Erika Gál 2007. - Archaeofauna, Equipo (Archaeofauna, 2008)
Archaeofauna, International Journal of archaeozoology